2018
DOI: 10.4070/kcj.2018.0048
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Left Axis Deviation in Acute Heart Failure Patients with Left Bundle branch block: an Analysis from the Korean Acute Heart Failure (KorAHF) Registry

Abstract: Background and ObjectivesThe prognostic impact of left axis deviation (LAD) on clinical outcomes in acute heart failure syndrome (AHFS) with left bundle branch block (LBBB) is unknown. The aim of this study was to determine the prognostic significance of axis deviation in acute heart failure patients with LBBB.MethodsBetween March 2011 and February 2014, 292 consecutive AHFS patients with LBBB were recruited from 10 tertiary university hospitals. They were divided into groups with no LAD (n=189) or with LAD (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…We noted that left axis deviation and first‐degree AVB were the only two ECG markers associated with all‐cause mortality. Left axis deviation has been shown in both population‐based studies 23 and in acute HF 24 to be associated with all‐cause mortality. Certainly, its role in cohorts of patients who do not have echocardiographic evidence of any type of HF though they have symptoms suspicious of HF and raised NTproBNP, like our cohort, had not been previously studied.…”
Section: Resultsmentioning
confidence: 99%
“…We noted that left axis deviation and first‐degree AVB were the only two ECG markers associated with all‐cause mortality. Left axis deviation has been shown in both population‐based studies 23 and in acute HF 24 to be associated with all‐cause mortality. Certainly, its role in cohorts of patients who do not have echocardiographic evidence of any type of HF though they have symptoms suspicious of HF and raised NTproBNP, like our cohort, had not been previously studied.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigations have been conducted during the last 5 decades to assess the significance of left axis deviation (≤−30°) in LBBB patients with ischemic and nonischemic cardiomyopathy. Some studies have suggested that the presence of left axis deviation during LBBB is the reflect of greater myocardial scarring tissue 11–15 . Other studies have supported a purely electrophysiological explanation for the left axis deviation with no discernible associations of structural characteristics (cardiac size, left ventricular dimensions or mass) or cardiac anatomic position with the QRS axis 16–19 .…”
Section: Discussionmentioning
confidence: 99%
“… 39) Other key messages and publications from KorAHF registry were summarized in Table 1 . 27) 29) 30) 31) 32) 33) 34) 35) 36) 37) 38) 39) 40) 41) 42) 43) 44) 45) 46) 47) 48) 49) 50) 51) 52) 53) 54) 55) 56) 57) 58) 59) 60) …”
Section: The Korean Acute Heart Failure Registry: Filling Gaps Of The...unclassified